Anecdotal Forensics, Phrenology, and Other Abject Lessons from the History of Science - Faigman, David L. (2008)
Many of the forensic identification sciences-including, among others, latent fingerprints, firearms, handwriting, and bitemarks- have little or no scientific foundation underlying them. They are largely based on anecdotal experience and supposition. In this way, anecdotal forensics closely resemble other historical failures of science, such as phrenology. Like phrenology, anecdotal forensics are based on inductive experience, have not been subjected to systematic tests, conform to expectations, prove what is already presumed to be known, and seem to have great practical utility for society. A century from now, however, the anecdotally-based beliefs of forensic experts are likely to survive much as phrenology endures today. They will be little more than abject lessons from the annals of the history of science. This Essay considers how it came to be that the law relies on expertise that is largely bereft of intellectual content and what should be done about it. As regards the former, the fault lies with both the professional forensic fields that privilege anecdote over rigorous test, as well as the lawyers and judges who accept forensic expertise uncritically. As regards the latter, although it is unrealistic to expect, and unreasonable to demand, the complete exclusion of anecdotal forensics from the trial process, its use should be sharply curtailed. This constriction, together with other basic reforms, might just be enough to render anecdotal forensics a historical curiosity and begin to establish a science-based forensic science